(untitled) (Palíndromo, 2018)
This paper, written as a letter, is addressed to performers, street artists, art educators and others interested in Urban Composition (Composição Urbana, C.U.): street performances. We start with the writing of letters to reach the discussion about what happens on the streets during the performances presented by the Research Group Corpos Informáticos and the artist ZMário, arriving at some considerations about relations between the art and the life in these respective productions. They are walks and dances that divert, defy, parade streets and crossroads; they are art works created individually or in groups that write the body in the city. The authors used are Careri, Derrida, Medeiros and Nietzsche.